Determinants Of Preventing Diarrhea in Children in Siulak Gedang Puskesmas In 2022 - Sela Indria Sari; Sari, Puspita; Asparian; Muhammad Ridwan; Marta Butar Butar; Solihin Sayuti (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2023)
Background: Diarrhea is a condition marked by changes in the shape and content of watery feces. It can also be accompanied by vomiting and bloody stools. Especially in the first three years of life, when the child may experience one to three episodes of severe diarrhea, this disease frequently affects children under the age of five. Aims: This study's objective was to determine the relationship between education level, knowledge, and attitudes of mothers in preventing diarrhea in toddlers in the working area of the Siulak Gedang Public Health Center, Kerinci Regency, 2022. Method: This kind of study is quantitative, cross-sectional, and uses 96 samples as its sample size. The Siulak Gedang Health Center in Kerinci Regency's operational region served as the site of this study. Proportional Random Sampling is the method of sampling. Without taking into account the strata in the population, proportional random sampling is a technique for taking samples at random. Results: According to the study's findings, 56.3% of people engage in effective actions for preventing diarrhea. According to statistical analyses, knowledge (0.000) and attitude (0.000) are the two factors that mothers' conduct in preventing diarrhea is connected with (0.000). Additionally, there is no connection between behavior used to prevent diarrhea and education level (0.338). Conclusion: There are relationship between the knowledge and attitudes of mothers with the prevention of diarrhea in children under five in the working area of the Siulak Gedang Health Center, Kerinci Regency.